Subversive Activities Initiative Constitutional Amendment
SUBVERSIVE ACTIVITIES. INITIATIVE CONSTITUTIONAL AMENDMENT. Declares existence, purposes, and objectives of world communist movement. Defines communist and subversive organizations and denies them political party status and property tax exemption. Prohibits members of such organizations or advocates of subversive doctrines from holding public office or employment with State or any public agency, or from receiving property tax exemption. Requires teachers and other employees of public educational institutions to answer congressional and legislative committee inquiries concerning communist affiliation and subversion. Imposes conditions on use of public buildings and property. Circa 1970s.